2010
DOI: 10.3201/eid1601.090401
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated Viral Gastroenteritis among Children in a Large Pediatric Hospital, United Kingdom

Abstract: Enteric viruses introduced from the community are major causes of these illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 37 publications
9
69
1
4
Order By: Relevance
“…Fourth, in this study, a nested PCR technique was used, which has greater sensitivity than the commonly used EIA. In contrast, for SaV, the proportion in our study (5.2%) was lower than that reported previously in Brazil (9.8%) 25 , and was similar to the rate found in the United Kingdom (5%) 7 .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Fourth, in this study, a nested PCR technique was used, which has greater sensitivity than the commonly used EIA. In contrast, for SaV, the proportion in our study (5.2%) was lower than that reported previously in Brazil (9.8%) 25 , and was similar to the rate found in the United Kingdom (5%) 7 .…”
Section: Discussioncontrasting
confidence: 56%
“…Epidemiological data have shown that both viruses are circulating around the world, with prevalence rates of 16.2-19.3% for HAdV detected by immunochromatography 4,5 and 0.8-5% for SaV 6,7 detected by reverse transcription polymerase chain reaction (RT-PCR). In Brazil, some investigations have reported HAdV and SaV infections among hospitalized children in the Northern Region, with prevalence rates of 2-10% and 2.5-5.9%, respectively, based on enzyme immunoassay (EIA), PCR, and RT-PCR methodologies [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…A United Kingdom study found 39% of all episodes of acute gastroenteritis (GE) among hospitalized patients were healthcare acquired and that rotavirus was the most common cause (31%). 1 Other studies documented that rotavirus accounted for up to 87% of paediatric HAGE cases. 5,6 A recent meta-analysis found that the incidence of healthcare-associated rotavirus infections was 8.1 per 100 hospitalizations for children under two years of age during epidemic months, 4 however a single-centre study suggested that the introduction of the rotavirus vaccine was associated with a substantial reduction in the incidence of both community and hospital-acquired rotavirus.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Although less frequently studied than HAI due to medical devices or surgical procedures, HAGE occurs frequently related to both endemic transmission as well as outbreaks. A United Kingdom study found 39% of all episodes of acute gastroenteritis (GE) among hospitalized patients were healthcare acquired and that rotavirus was the most common cause (31%).…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of AGE often occur in clusters, such as schools, camps, and daycare centers. Previous studies in children were mainly focused on community-acquired infection, but more recently, healthcare-associated adenoviral AGE is being more closely studied [44,[46][47][48]. Along with rotavirus and norovirus, adenovirus has emerged as one of the leading causes of viral AGE in both these settings, with immunocompromised patients possibly infected with multiple viruses and shedding viruses in their stools for prolonged periods [47,48].…”
mentioning
confidence: 99%